Assessing the Impact of the National Health Insurance Program (JKN) on Healthcare Access in City Medan - Sihotang, Mujuranto; Simangunsong, Humala (Law and Economics, 2022)
Assessing the Impact of the National Health Insurance Program (JKN) on Healthcare Access in City Medan. This research evaluates the impact of the National Health Insurance Program (JKN) on healthcare access in City Medan, Indonesia. Implemented with the goal of providing equitable and affordable healthcare services to all citizens, JKN has undergone scrutiny to assess its effectiveness in improving healthcare access and outcomes. Employing a mixed-methods approach, this study amalgamates quantitative surveys and qualitative interviews. Stratified sampling was utilized to collect data from diverse socio-economic groups across City Medan. Quantitative surveys focused on healthcare utilization patterns, awareness of JKN benefits, and demographic factors, while qualitative interviews explored nuanced perspectives, barriers to access, and suggestions for improvement. The analysis reveals a notable increase in healthcare utilization and improved accessibility to essential services following JKN implementation. However, disparities in service quality across healthcare facilities persist, coupled with geographical barriers and administrative complexities hindering seamless service provision. Maternal and child health indicators show promise, and preventive healthcare practices are gaining traction, indicating a shift towards proactive health-seeking behaviors. The research underscores the necessity for policy refinements, targeted interventions, technological innovations, community engagement, and efficient resource allocation to strengthen JKN's effectiveness. Strategic recommendations advocate for streamlined administrative processes, service quality enhancements, and geographical outreach to remote communities